Twin pregnancy and postpartum haemorrhage: a systematic review and meta-analysis - Fatma A. M. Abdulsalam; Natalie E. Bourdakos; James W. F. Burns; Zoe Y. Zervides; Nathanael Q. E. Yap; Maamoun Adra; Hayato Nakanishi; Christian A. Than; Francis A. Chervenak; Sir Sabaratnam Arulkumaran (BMC, 2024)
Abstract Background Postpartum haemorrhage (PPH) continues to stand as the primary cause of maternal morbidity and mortality post-delivery, with twin pregnancies carrying a heightened risk of PPH compared to singleton deliveries. Objectives To investigate the incidence of primary PPH among twin pregnancies and report on maternal and peripartum characteristics within this population. Methods A literature search was conducted using data from PubMed, EMBASE, Cochrane, Scopus, and Web of Science. The search aimed to identify studies concerning mothers with twin pregnancies and postpartum haemorrhage (PPH) from the inception of each respective database to June 8th, 2023. Pooled means and proportions were analyzed using the generic inverse variance method. This review was registered prospectively with PROSPERO (CRD42023427192). Results A total of 21 studies involving 23,330 twin pregnant patients were included. Incidence of PPH for vaginal delivery and Caesarean delivery (CS) was found to be 10.9% (95% CI: -0.017, 0.235, I2 = 96%) and 27.0% (95% CI: 0.180, 0.359, I2 = 99%) respectively. In vitro fertilization (IVF) was the most common conception method at 62.0% (95% CI: 0.448, 0.792, I2 = 100%) with 81.1% (95% CI: 0.708, 0.915, I2 = 100%) of twins being dichorionic diamniotic. Conclusion This meta-analysis demonstrated more than one in ten vaginal deliveries and over one in four cesarean sections result in PPH for twin pregnancies. IVF is the predominant method of conception in this patient group and seems to contribute to subsequent PPH risk in specific mothers. While preliminary, these findings underscore the necessity for further well-designed and high-quality studies to validate these results.